Analisis Kemudahan Penggunaan Aplikasi Dompet Digital Indonesia (GoPay) dengan Menggunakan Metode TAM - Panggabean, Riski Melisa; Harianja, Chindy Lorenza; Saputra, Imam (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Digital wallet applications or technology-based payment services have become payment tools that are inseparable from everyday life in Indonesian society. Digital wallet applications in Indonesia have become a very important need for society to carry out transactions quickly and safely using smartphones. Even though the Indonesian digital wallet application makes transactions very easy, there are often problems that cause delays in receiving funds from service providers, low digital literacy makes users become victims of online fraud, and lack of application security which can cause users to switch to other services. There are many digital wallet applications in Indonesia that make transactions easy, one of which is GoPay. GoPay is a popular digital wallet application that provides various features for making digital payments. This research aims to determine the ease of use of the GoPay application with the presence of GoPay as a transaction service. This research uses the Technology Acceptance Model (TAM) method. This research measures user perceptions of ease of use and usefulness. The method used is a quantitative approach with data collection techniques by distributing questionnaires with a sample size of 100 respondents who are active users of the GoPay application. Data was collected through an online questionnaire and processed using statistical data processing software (SPSS). The survey of respondents showed that the PEOU indicator variable had a percentage of 98%, the PU indicator variable had a percentage of 89%, the ATU indicator variable had a percentage of 98%, and the ITU indicator variable had a percentage of 85%, and the ASU indicator variable had a percentage of 89%. The research results show that the two TAM constructs, namely ease of use and usefulness, have a significant positive influence on intention to use GoPay. These findings confirm that the variables of perceived usefulness, attitude of use, behavior of use, and actual conditions of use influence the level of ease of use of GoPay.